A rare and overlooked mechanical complication of partial nephrectomy: Accelerated hypertension due to renal artery stenosis - Yusuf Ziya Şener; Uğur Canpolat; Mustafa Sertaç Yazıcı; Enver Atalar (KARE Publishing, 2019)
Secondary hypertension accounts for 5% to 10% of all hypertensive cases, and renal artery stenosis is one of the most common causes of secondary hypertension. Although atherosclerotic vascular disease and fibromuscular dysplasia are the leading causes of renal artery stenosis, there are other, rare etiologies, such as vasculitis and trauma. A partial nephrectomy is the standard of care treatment option for early stage renal carcinoma patients. Traumatic renal artery stenosis can occur during this surgical intervention, though it is a very rare adverse event, and only a few case reports have been reported in the literature. This report is the description of successful percutaneous treatment of accelerated hypertension secondary to traumatic renal artery stenosis after a partial nephrectomy.